2017
DOI: 10.1108/et-10-2015-0096
|View full text |Cite
|
Sign up to set email alerts
|

Transition from school-based training in VET

Abstract: Purpose-To assess the drop-out rate among disadvantaged students within vocational education and training (VET). The article examines the probability of dropping out after school-based training for child welfare clients-a particularly disadvantaged group of youth. Child welfare clients' drop-out rate is compared with students from a representative sample of their peers. Design/methodology/approach-Average marginal effects (AME) were calculated from multinomial logistic regression models. Data were from public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
2
0
4
Order By: Relevance
“…Social networks, especially the mother’s networks (Roth, 2014), have also been found to be important for the chances of finding an apprenticeship, which leads to greater difficulties in finding an apprenticeship when the social networks are weaker, for example, among immigrants (Helland & Støren, 2006) or disadvantaged youth (Brahm, Euler, & Steingruber, 2014; Schmidt, 2010). Findings from Norway, which has an apprenticeship system similar to the one in Denmark, also suggest that one of the reasons for the high dropout rate among youth from OHC is the discontinuity of their educational pathway before finding an apprenticeship (Dæhlen, 2017). However, the school‐based system stratifies (indirectly or directly) through previous educational achievements, which is shown to have a strong impact on future development for youth from OHC (Berlin et al, 2011; Forsman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Social networks, especially the mother’s networks (Roth, 2014), have also been found to be important for the chances of finding an apprenticeship, which leads to greater difficulties in finding an apprenticeship when the social networks are weaker, for example, among immigrants (Helland & Støren, 2006) or disadvantaged youth (Brahm, Euler, & Steingruber, 2014; Schmidt, 2010). Findings from Norway, which has an apprenticeship system similar to the one in Denmark, also suggest that one of the reasons for the high dropout rate among youth from OHC is the discontinuity of their educational pathway before finding an apprenticeship (Dæhlen, 2017). However, the school‐based system stratifies (indirectly or directly) through previous educational achievements, which is shown to have a strong impact on future development for youth from OHC (Berlin et al, 2011; Forsman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Vocational programmes in Denmark differ significantly from those in Finland in that they provide a smoother transition from school to work by including apprenticeship-based workplace training in addition to school-based training ( Cederberg & Hartsmar, 2013 ). Findings from Norway (with a similar apprentice-based training system of vocational education to that of Denmark) suggest that child welfare clients have difficulties in obtaining apprenticeships, which prevents them from completing the programme ( Dæhlen, 2017 ). Moreover, a study comparing the Nordic countries ( Kääriälä et al, 2018 ) showed that children in care fail to complete secondary education more often than their peers.…”
Section: Discussionmentioning
confidence: 99%
“…El impacto económico y social del abandono temprano, en todos los niveles educativos, es una preocupación que afecta a los países avanzados y a las sociedades tecnificadas en general (Aarkrog et al, 2018;Daehlen, 2017;Lovat, 2016;Moreno Herrera et al, 2016). Aunque no existen estudios específicos sobre el coste económico del abandono en la FP superior en España, podemos utilizar los datos y cifras del abandono universitario como referente para centrar el problema en esta etapa educativa concreta, con ciclos formativos por lo general de dos mil horas, que se organizan en dos cursos académicos.…”
Section: El Problema Del Abandono En La Educación Superiorunclassified